2016
DOI: 10.1016/j.drugalcdep.2015.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness meditation improves emotion regulation and reduces drug abuse

Abstract: These results indicate that promoting emotion regulation and improving ACC/mPFC brain activity can help for addiction prevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
111
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(133 citation statements)
references
References 33 publications
11
111
1
10
Order By: Relevance
“…Although the results from human studies neither support nor refute the neuroprotective benefits of environmental enrichment, research has recently become focused on developing cognitive training, such as working memory and mindfulness exercises, for attenuating and/ or preventing neuroplastic changes associated with these disorders (Rogers, Ferrari, Mosely, Lang, & Brennan, 2017;Ruffault et al, 2016;Chiesa & Serretti, 2014;Karyadi, VanderVeen, & Cyders, 2014;Lee, An, Levin, & Twohig, 2015;Tang, Tang, & Posner, 2016;Bega, GonzalezLatapi, Zadikoff, & Simuni, 2014;Corbett, Jeffers, Nguemeni, GomezSmith, & Livingston-Thomas, 2015;Milgram, Siwak-Tapp, Araujo, & Head, 2006;Zigmond & Smeyne, 2014).…”
Section: Interestingly Mccool and Chappell Found Socially Housed Longmentioning
confidence: 99%
“…Although the results from human studies neither support nor refute the neuroprotective benefits of environmental enrichment, research has recently become focused on developing cognitive training, such as working memory and mindfulness exercises, for attenuating and/ or preventing neuroplastic changes associated with these disorders (Rogers, Ferrari, Mosely, Lang, & Brennan, 2017;Ruffault et al, 2016;Chiesa & Serretti, 2014;Karyadi, VanderVeen, & Cyders, 2014;Lee, An, Levin, & Twohig, 2015;Tang, Tang, & Posner, 2016;Bega, GonzalezLatapi, Zadikoff, & Simuni, 2014;Corbett, Jeffers, Nguemeni, GomezSmith, & Livingston-Thomas, 2015;Milgram, Siwak-Tapp, Araujo, & Head, 2006;Zigmond & Smeyne, 2014).…”
Section: Interestingly Mccool and Chappell Found Socially Housed Longmentioning
confidence: 99%
“…In agreement with the statements that point to anxiety reduction as one of the effects after meditation, one study found that the mindfulness meditation practice can help a person gain the ability to cope with their emotions, helping to deal with anxieties and cravings related to the drug (21) .…”
Section: After a Meditation Group The Patients Leave Very Calmly (E1)mentioning
confidence: 60%
“…The term mindfulness refers to the ability to be aware of the present moment in physical sensations, perceptions, thoughts and feelings, without judgment (19) . With the origin in traditions such as Buddhism, yoga and Taoism, its practice was integrated with behavioral medicine, especially in stress reduction programs, and is currently being practiced in the treatment of addictions (21) .…”
Section: Encourage Them To Participate In the Meditation Group (E2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Deplus [40] showed that attention awareness group interventions enhanced the ability to adjust the excitement in teenagers. Tang [41] presented a research where attention awareness as a mediating agent can increase self-control for excitement regulation.…”
Section: Discussionmentioning
confidence: 99%